Bridging Global Protocols and Local Wisdom: Innovating Refugee Assistance Through a Harmonized Protection Model - Rahman, Malahayati; Rasyid, Laila M.; Sastro, Marlia; Rahmi, Agustia (Faculty of Law, Jambi University, 2024)
This paper examines the critical need to integrate the Global Protection Cluster (GPC) approach with local knowledge to improve the effectiveness of refugee aid programs. It analyses the foundational principles of the GPC method in conjunction with the valuable insights provided by indigenous knowledge systems, proposing a comprehensive model to align global strategies with local realities. The study highlights the multifaceted advantages of this integrated approach through an extensive literature review and illustrative case studies from various contexts, including Afghanistan, Jordan, Uganda, Ethiopia, and Indonesia. Particular emphasis is placed on the Rohingya refugee situation in Aceh, which serves as a pivotal case study demonstrating the transformative potential of incorporating local wisdom into program design. The paper advocates for a participatory model that prioritizes the active involvement of displaced communities in decision-making processes, ensuring that aid programs are culturally competent and responsive to refugees' specific needs. Key recommendations are provided for a wide range of stakeholders—policymakers, practitioners, organizations, and donors—emphasizing the importance of collaborative partnerships, adaptive program design, and community-led initiatives. The findings suggest that by embracing local knowledge and fostering inclusive participation, refugee aid programs can achieve greater sustainability and effectiveness, ultimately contributing to more resilient and empowered displaced populations.